An ultrafast responsive BODIPY-based fluorescent probe for the detection of endogenous hypochlorite in live cells. Issue 3 (20th December 2016) - Qiao, Liang; Nie, Hailiang; Wu, Yulong; Xin, Fangyun; Gao, Congcong; Jing, Jing; Zhang, Xiaoling
Abstract : An ultrafast responsive BODIPY-based fluorescent probe was synthesized to selectively detect endogenous hypochlorite in live cells. Abstract : Hypochlorite plays a significant role in various physiological and pathological processes; however, its role is still less clear than the role of other reactive oxygen species. Herein, we report an ultrafast responsive (<0.2 s) and highly selective probe B-Ts for hypochlorite with high sensitivity and a detection limit as low as 7.5 nM. The probe was compatible in a wide pH range of 4–13. More importantly, experiments in live cells showed that the probe could penetrate the cell membrane easily and was capable of imaging endogenous and exogenous hypochlorite specifically with a fast response.